Lexical Indigenisms in Archbishop Cortés y Larraz’s Descripción geográfico-moral (1770): Some Salvadora Data - Ramírez Luengo, José Luis (2019)
This paper aims to be an attempt to decrease the lack of studies about the lexical history of Central American Spanish, so its main goal is to analyse Indigenous lexical items (indigenisms) that can be found in the chapters devoted to El Salvador in the Descripción geográfica-moral de la diócesis de Goathemala, a chronicle written in 1770 by Pedro Cortés y Larraz, archbishop of Guatemala. Thus, issues like etymological origin of indigenisms, their integration degree, semantic fields where they are used or items that can be considered as americanisms from a dynamic and usage point of vieware taken into account. The final purpose of the analysis is to detect diatopically marked words and to describe the dialectalization of this linguistic level that, by means of indigenisms, can be discovered in this region at the end of 18thcentury.